2002
DOI: 10.1143/jjap.41.1763
|View full text |Cite
|
Sign up to set email alerts
|

A New Efficient Error Correctible Modulation Code for Holographic Data Storage

Abstract: Paramagnetic colloidal particles move in the potential energy landscape of a magnetically modulated bubble lattice of a magnetic garnet film. The modulation causes the energy minima to alternate between positions above the centres of the bubbles and interstitial positions. The particles deterministically follow the time-dependent positions of the energy minima until the minima become unstable in one or several directions and allow the particles to hop to a new minimum. We control the time delay between instabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…The 9:12 pseudo-balanced code (Hwang et al, 2002) is a strip code which maps 9-bit information into a 12-bit codeword with a code rate of ¾. It is similar to the 8:12 balanced modulation code, but with higher code rate by relaxing the balanced constraint to allow certain degree of codeword imbalance.…”
Section: :12 Pseudo-balanced Strip Codementioning
confidence: 99%
See 1 more Smart Citation
“…The 9:12 pseudo-balanced code (Hwang et al, 2002) is a strip code which maps 9-bit information into a 12-bit codeword with a code rate of ¾. It is similar to the 8:12 balanced modulation code, but with higher code rate by relaxing the balanced constraint to allow certain degree of codeword imbalance.…”
Section: :12 Pseudo-balanced Strip Codementioning
confidence: 99%
“…Then the Viterbi algorithm finds the best state sequence using those aforementioned distances as branch metrics. In (Hwang et al, 2002), it is shown that the 9:12 pseudo-balanced code, though with a higher code rate, provides similar performance as the 8:12 balanced strip code.…”
Section: :12 Pseudo-balanced Strip Codementioning
confidence: 99%
“…1) However, because of the denser recording and faster readout of data in HDDS, severe noise and impairment can occur in the retrieved data; therefore, it requires an effective signal processing scheme for reliable data readout. [2][3][4] Low-density parity-check (LDPC) codes have a performance near the Shannon limit when decoded using an iterative probabilistic decoding algorithm. Also, they have a low error floor with a large minimum distance and a highly parallel decoding scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in previous research, a 9 : 12 pseudo balanced code (PBC) error correctible modulation code using the Viterbi algorithm is proposed and evaluated. 3) Similarly, we propose the error correctible balanced code that uses section dividing and parity appending. Also, we use a codeword look-up table with 2 as a hamming distance.…”
Section: Introductionmentioning
confidence: 99%